Baltijas jūras reģiona ilgtspējīgas attīstības nākotnes perspektīvas - Ūgainis, Kristaps (Latvijas Universitāte, 2020)
Bakalaura darba nosaukums: “Baltijas jūras reģiona ilgtspējīgas attīstības nākotnes perspektīvas”. Par darba mērķi tika izvirzīts noskaidrot kā izvēlētās ilgtspējīgās attīstības dimensijas – ekonomikas, vides un inovāciju darbojas Baltijas jūras reģionā un kāda ir to ietekme uz reģiona ilgtspējīgu attīstību. Par darba hipotēzi tika izvirzīts: Baltijas jūras reģiona valstu atšķirīgie ilgtspējīgas attīstības dimensiju un indikatoru rādītāji kavē Baltijas jūras reģiona ilgtspējīgu attīstību. Lai apstiprinātu vai noliegtu izvirzīto hipotēzi darbā tika uzstādīti sekojoši uzdevumi: •Apzināt ilgtspējīgas attīstības principus un konceptuālās interpretācijas; •Apzināt ilgtspējīgas attīstības dimensiju un indikatoru nozīmi; •Darba otrajā daļā apkopot un izanalizēt Baltijas jūras reģiona valstu indikatoru rādītājus; •Izdarīt secinājumus par ekonomikas indikatoru attīstības tendencēm; •Izdarīt secinājumus par vides indikatoru attīstības tendencēm; •Izdarīt secinājumus par inovāciju attīstības tendencēm; •Izdarīt secinājumus par dimensiju darbību reģionā pamatojoties uz iepriekš apskatītiem pīlāriem un reģiona ilgtspējīgas attīstības perspektīvu. Izvirzītie uzdevumi tika veiksmīgi izpildīti un darbā izvirzītā hipotēze neapstiprinājās, jo pēc izpildītiem darbā uzstādītajiem mērķiem tika secināts, ka Baltijas jūras reģiona valstu atšķirīgie ilgtspējīgas attīstības dimensiju un indikatoru rādītāji nekavē Baltijas jūras reģiona ilgtspējīgu attīstību. Atslēgvārdi: Baltijas jūras reģions, Ilgtspējīga attīstība, Ilgtspējas dimensijas

Title of the bachelor's thesis: "Baltic Sea region sustainability perspectives in the future". The aim of the work was to find out how the chosen dimensions of sustainable development - economy, environment and innovation operate in the Baltic Sea region and what is their impact on the sustainable development of the region. The working hypothesis was put forward: The different indicators of sustainable development dimensions and indicators of the Baltic Sea region countries hinder the sustainable development of the Baltic Sea region. In order to confirm or deny the proposed hypothesis, the following tasks were set in the work: •To identify the principles and conceptual interpretations of sustainable development; •Identify the importance of sustainable development dimensions and indicators; •In the second part of the work to summarize and analyze the indicators of the Baltic Sea region indicators; •To draw conclusions about the development trends of economic indicators; •To draw conclusions about the development trends of environmental indicators; •To draw conclusions about innovation development trends; •Draw conclusions on the functioning of the dimensions in the region based on the pillars discussed above and the perspective of sustainable development of the region. The set tasks were successfully fulfilled and the hypothesis set in the work was not confirmed, because after meeting the set goals, it was concluded that the different indicators of sustainable development dimensions and indicators of the Baltic Sea region do not hinder the sustainable development of the Baltic Sea region. Keywords: Baltic Sea Region, Sustainable Development, Dimensions of Sustainability• Draw conclusions about the perspective of sustainable development in the Baltic Sea region. The hypothesis put forward in the course of the work was not confirmed, because after the goals set in the work were fulfilled, it was concluded that the co-operation of the Baltic Sea region countries is close in all areas, despite their different development rates and indicators. Key words: Baltic Sea region, sustainable development, dimensions of Sustainability
Baltic Sea region sustainability perspectives in the future
Keywords: Politikas zinātne; Baltijas jūras reģions; Ilgtspējīga attīstība; Baltijas jūra; Ilgtspējas dimensijas; Sustainable development